Effect of sustained high-intensity exercise on executive function - Kana Konishi; Tetsuya Kimura; Atsushi Yuhaku; Toshiyuki Kurihara; Masahiro Fujimoto; Takafumi Hamaoka; Kiyoshi Sanada (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Exercise-induced changes in executive function affect the control of action in a dynamic environment. This study aimed to examine the effect of sustained high-intensity exercise on executive function. Nine healthy male and female participants (age, 21-28 years) completed an exercise session with 65-min treadmill running at 75% VO2max. Executive function was assessed before and after exercise with the Stroop Color and Word Test that included congruent and incongruent conditions. The reaction time and response accuracy of the test were measured, and the task difficulty was controlled by adjusting the stimulus duration so that each participant could maintain at least 80% response accuracy to exclude the effect of a speed-accuracy trade-off. The levels of plasma norepinephrine and adrenocorticotropic hormone were examined. A significant interaction with the reaction time was found (condition × time, P = 0.024), in which the reaction time significantly increased after exercise only in the incongruent condition (P = 0.019). The response accuracy was not significantly different between before and after exercise in both conditions, which indicated that the response accuracy was controlled as intended. The levels of plasma norepinephrine and adrenocorticotropic hormone were significantly increased after exercise (P < 0.05). These results demonstrated that the reaction time in the incongruent condition increased after sustained high-intensity exercise with a cognitive function test with the response accuracy controlled, indicating a decline in executive function. Increased levels of plasma norepinephrine and adrenocorticotropic hormone may contribute, at least in part, to such decline in executive function.